New Caledonia's enigmatic terrestrial diving beetle Typhlodessus monteithi is a derived species of Paroster - Villastrigo, Adrián; Deharveng, Louis; Balke, Michael (Zoologica scripta, 2023)
The classification of highly adapted species in well‐studied clades may be obscured by convergent character evolution. This is for example the case in aquatic lineages adapted to subterranean (and shallow subterranean) habitats, in which species usually possess reduced eyes and wings as well as translucent cuticles. In 1985, the terrestrial diving beetle genus and species Typhlodessus monteithi Brancucci (Coleoptera: Dytiscidae) was described from a shallow subterranean habitat in New Caledonia. Until now, the systematic classification of Typhlodessus remains unclear, as it could not be assigned to any of the known tribes of the subfamily Hydroporinae. Here, we reveal this species' phylogenetic position and evolutionary history. We obtained molecular data from an almost 30 years old museum specimen and performed phylogenetic analyses using complete mitochondrial genomes and nuclear markers, which resulted in the placement of Typhlodessus monteithi within the subtribe Sternopriscina, as a junior synonym of the genus Paroster. The genus Paroster contains epigean, stygobitic as well as two other terrestrial Australian species. Our finding extends the geographical distribution of Paroster to New Caledonia. Adaptation to terrestrial habitats in Paroster species may be a way to survive in hyper humid environments that however might lack suitable lentic habitats.